Variational mechanics of water at biological interfaces - Fernandez, Ariel (2011)
A variational principle governing nanoscale water configurations at biological interfaces is derived. The underlying functional determines a scalar field g=g(r) indicating the expected hydrogen-bond coordination of water at position r, and includes an elastic term to penalize local coordination losses. The minimization of interfacial free energy implies that g must obey a Poisson-type equation with Dirichlet boundary conditions. The equation is integrated and the specialization of the treatment to protein-water interfaces enables the determination of protein complexation propensities and the identification of protein binding sites and binding hot spots.